Part 3: Disciplines in an active voice. Issue 3 (1st December 2019) - Infante Mora, Eva; Greenwood, Davydd; Ivanchikova, Melina; Castilla-Vázquez, Carmen; Cid-Rodríguez, Rafael; Miranda Díaz, Bartolomé; Flores-Macías, Gustavo A.
Abstract : This section of the account of the action research and thorough reform of the CASA-Sevilla study abroad programme describes how the courses in the fields of anthropology, history and art / art history were changed. It explains why a pedagogical reform was needed, the choices faculty members made and the difficulties they faced. Transitioning to an active pedagogy has not been an easy path for faculty. The accounts show how they integrated independent intercultural research into their classes and how they reacted to their new roles as intercultural mentors. It also includes a description of the faculty member-in-residence's role in the programme and reflections on the reform by the faculty member who served as Cornell representative in CASA-Sevilla during the 2016–2017 academic year.